Serrated polyposis: rapid and relentless development of colorectal neoplasia - Edelstein, Daniel L; Axilbund, Jennifer E; Hylind, Linda M; Romans, Katharine; Griffin, Constance A; Cruz-Correa, Marcia; Giardiello, Francis M (Gut, 2013)
Objective Serrated (hyperplastic) polyposis (SP) is a rare disorder with multiple colorectal hyperplastic polyps and often sessile serrated adenomas/polyps (SSA/P) or adenomas. Although associated with colorectal cancer, the course of SP is not well described. Design 44 patients with SP were studied. The results of 146 colonoscopies with median follow-up of 2.0 years (range 0–30) and a median of 1.0 years (range 0.5–6) between surveillance colonoscopies were evaluated. Findings from oesophogastroduodenoscopy examinations were analysed. Results The mean age at diagnosis of SP was 52.5±11.9 years (range 22–78). In two pedigrees (5%) another family member had SP. None of 22 patients had gastroduodenal polyps. All patients had additional colorectal polyps at surveillance colonoscopy. SSA/P or adenomas were found in 25 patients (61%) at first colonoscopy and 83% at last colonoscopy. Recurrent SSA/P or adenomas occurred in 68% of patients at surveillance colonoscopy. Three patients had colorectal cancer. Eleven patients (25%) underwent surgery (mean time from diagnosis of SP 2.0±0.9 years). After surgery all seven surveyed patients developed recurrent polyps in the retained colorectum (4/7 had SSA/P or adenomas). No association was found between colorectal neoplasia and sex, age at diagnosis of SP or initial number of colorectal polyps. Conclusions In SP, rapid and unrelenting colorectal neoplasia development continues in the intact colorectum and retained segment after surgery. These findings support the possibility of annual colonoscopic surveillance, consideration for colectomy when SSA/P or adenomas are encountered and frequent postoperative endoscopic surveillance of the retained colorectum.